Not All Selfies Took Alike: Distinct Selfie Motivations Are Related to Different Personality Characteristics - Etgar, Shir; Amichai-Hamburger, Yair (Frontiers in Psychology, 2017)
Selfies have become a frequent and commonplace occurrence, though the reasons which lead people to take selfies remain unclear. This research explores what motivates selfie- taking, and suggests that this is not a uniform phenomenon and varying motivations may be found among selfie- takers. In addition, the connection between these distinct selfie motivations and personality characteristics, including the big five, narcissism and self-esteem, as well as types of selfie behaviors are examined. At the first stage of the research, one hundred and seventeen participants filled out a questionnaire dealing with their reasons for taking selfies. An explanatory factor analysis revealed three distinct selfie motivations: self-approval, belonging, and documentation. At the second stage, one hundred and ninety-one different participants answered both the same questionnaire, and personality traits questionnaires. A confirmatory factor analysis verified that the three selfie motivations model has a good fit. Our results suggested that each selfie- motivator is differently related to personality characteristics: self-approval was negatively related to: conscientiousness, emotional stability, openness to experiences, and self-esteem, and positively correlated to frequent checking for "likes". Belonging was related to openness to experiences. Documentation was related to agreeableness and extroversion. Unlike previous studies, none of the selfie- motivating factors was found to relate to narcissism. The reasons for these differences, as well as the need to refer to selfie- taking as a multidimensional phenomenon, are discussed.